Tumor suppressor microRNAs: A novel non‐coding alliance against cancer. Issue 16 (26th March 2014) - Blandino, Giovanni; Fazi, Francesco; Donzelli, Sara; Kedmi, Merav; Sas-Chen, Aldema; Muti, Paola; Strano, Sabrina; Yarden, Yosef
Abstract : Tumor initiation and progression are the outcomes of a stepwise accumulation of genetic alterations. Among these, gene amplification and aberrant expression of oncogenic proteins, as well as deletion or inactivation of tumor suppressor genes, represent hallmark steps. Mounting evidence collected over the last few years has identified different populations of non‐coding RNAs as major players in tumor suppression in almost all cancer types. Elucidating the diverse molecular mechanisms underlying the roles of non‐coding RNAs in tumor progression might provide illuminating insights, potentially able to assist improved diagnosis, better staging and effective treatments of human cancers. Here we focus on several groups of tumor suppressor microRNAs, whose downregulation exerts a profound oncologic impact and might be harnessed for the benefit of cancer patients.